2016
DOI: 10.1637/11398-022616-resnote.1
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Sensitivity ofAvibacterium paragallinarumIsolates from Four Latin American Countries

Abstract: The antimicrobial sensitivity of 11 reference strains and 66 Avibacterium paragallinarum isolates from four Latin American countries was investigated. All 11 reference strains were sensitive to amoxicillin-clavulanic acid, ampicillin, fosfomycin, gentamicin, kanamycin, neomycin, penicillin, tetracycline, and trimethoprim-sulfamethoxazole. The 11 reference strains were all resistant to lincomycin. All isolates (100%) from Mexico, Panama, and Peru were sensitive to amoxicillin-clavulanic acid, ampicillin, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
3
11
0
1
Order By: Relevance
“…A total of seven publications investigated phenotypic resistance in 143 A. paragallinarum isolates from diseased flocks in Asia (India, Thailand, Indonesia, Taiwan) ( 63 – 67 ), Africa (Uganda) ( 68 ), and the Americas (Mexico, Ecuador, Peru, Panama) ( 5 ). All studies used the disk diffusion test, except one where broth microdilution ( 64 ), and one where agar dilution ( 68 ) tests were used (Table 4 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of seven publications investigated phenotypic resistance in 143 A. paragallinarum isolates from diseased flocks in Asia (India, Thailand, Indonesia, Taiwan) ( 63 – 67 ), Africa (Uganda) ( 68 ), and the Americas (Mexico, Ecuador, Peru, Panama) ( 5 ). All studies used the disk diffusion test, except one where broth microdilution ( 64 ), and one where agar dilution ( 68 ) tests were used (Table 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…A study on isolates from Latin American countries ( 5 ) showed the lowest level of resistance against co-trimoxazole (potentiated sulfonamide). However, the authors remind that sulfonamides should be administered with caution in poultry given their low safety margin and the presence of residues in meat and eggs for a relatively longer period ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strain was identified as A. paragallinarum serovar C-2 using the morphology of the colony, biochemical tests (catalase test, oxidase test, urease test, peptone test, and carbohydrate fermentation, such as that of maltose, mannitol, lactose, and sorbitol) (11), specific PCR (12), and hemagglutination inhibition (HI) (13). The disk diffusion test (14) revealed resistance to colistin, ampicillin, sulfamethoxazole-trimethoprim, penicillin, neomycin, lincomycin, oxacillin, enrofloxacin, and gentamicin. The strain was susceptible to amoxicillin-clavulanic acid, doxycycline, streptomycin, florfenicol, tiamulin, levofloxacin, and gatifloxacin.…”
Section: Announcementmentioning
confidence: 99%
“…The magnitude of usage is expected to increase considerably over coming years due to intensification of farming practices in much of the developing world [4]. Much of our knowledge and assumptions on the prevalence and evolution of AMR in animal production systems relate to organisms that more often than not are commensal in poultry such as Escherichia coli [5], Enterococcus spp., and Staphylococcus aureus [6] as well as foodborne zoonotic pathogens, such as non-typhoid Salmonella (NTS) [7] and Campylobacter spp. [8].…”
Section: Introductionmentioning
confidence: 99%